Respuesta :
Answer:
(- 2, 3 )
Step-by-step explanation:
Given the 2 equations
4x + 3y = 1 → (1)
x - 3y = - 11 → (2)
Adding the 2 equations term by term will eliminate the y- term
5x + 0 = - 10
5x = - 10 ( divide both sides by 5 )
x = - 2
Substitute x = - 2 into either of the 2 equations and solve for y
Substituting into (1)
4(- 2) + 3y = 1
- 8 + 3y = 1 ( add 8 to both sides )
3y = 9 ( divide both sides by 3 )
y = 3
solution is (2, - 3 )
Answer:
x=-2, y=3
Step-by-step explanation:
4x + 3y = 1.......... Equ 1
x - 3y = -11...........Equ 2
5x=-10
x=-2
From equ 1
4x + 3y =1
4(-2)+3y=1
-8+3y=1
3y=1+8
3y=9
y=3